Environmental reporting practices in Malaysia: is it a mechanism for corporate accountability and stakeholder engagement? / Haslinda Yusoff and Faizah Darus. - Yusoff, Haslinda; Darus, Faizah (Universiti Teknologi MARA Selangor, 2012)
Environmentally-related practices among business corporations in Malaysia have received considerable attention from various groups of stakeholders. This study explores environmental reporting practices in Malaysia and emphasizes that the reporting practices serve as a means of communicating corporate accountability with a view to improving business-stakeholders relationship. A questionnaire survey was undertaken among Malaysian public listed companies to obtain information concerning their environmental reporting practices and their recognition of various relevant stakeholder groups. Corporate managers were selected as the sample for the purpose of administering the survey. A total of 141 responses were received out of which only 31 companies (22%) carried out some form of environmental reporting. These companies constituted the final sample for the study. The results of the survey indicate that corporate managers have taken positive steps in implementing environmental reporting practices. The positive steps include having various means of reporting, identifying stakeholder groups and engaging with them. The results also reveal that companies engage in environmental reporting to enhance their corporate image and to discharge their corporate accountability in meeting stakeholders’ information demands.